2017
DOI: 10.3389/fmicb.2017.00818
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Genetic Diversity and Antimicrobial Resistance Profiles of Campylobacter jejuni Recovered from Cattle and Humans

Abstract: Campylobacter jejuni, a leading cause of gastroenteritis in humans, is a foodborne pathogen that can reside in chickens, pigs, and cattle. Because resistance to fluoroquinolones and macrolides, which are commonly used to treat human infections, has emerged in C. jejuni, it is imperative to continously monitor resistance patterns and examine the genetic variation in strains from human infections and animal reservoirs. Our previous study of C. jejuni from human campylobacteriosis cases showed a significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
39
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 36 publications
7
39
3
1
Order By: Relevance
“…Fluoroquinolone resistance amongst human and farm animal isolates of C. jejuni has been reported extensively [10,41]. Previous studies have reported correlation between ciprofloxacin resistance (and the T86I mutation) and specific clonal groups of C. jejuni [10,18,19,42,43]. In a six year study of 3300 human C. jejuni isolates in Oxfordshire, UK, nine clonal complexes were significantly associated with ciprofloxacin sensitivity ( [44].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolone resistance amongst human and farm animal isolates of C. jejuni has been reported extensively [10,41]. Previous studies have reported correlation between ciprofloxacin resistance (and the T86I mutation) and specific clonal groups of C. jejuni [10,18,19,42,43]. In a six year study of 3300 human C. jejuni isolates in Oxfordshire, UK, nine clonal complexes were significantly associated with ciprofloxacin sensitivity ( [44].…”
Section: Discussionmentioning
confidence: 99%
“…The other four PFGE types belonged to ST982 (type B) and ST52 (types C, D, and E). ST982 accounted for 20.8% (10/48) of the C. jejuni isolates in a previous study involving a lamb slaughterhouse, and it was also reported in cattle (15,25,49). ST52 was reported sporadically in C. jejuni isolates from different countries and sources, including from ruminants (36-38, 48, 50, 51).…”
Section: Discussionmentioning
confidence: 61%
“…In contrast to the C. coli isolates, the predominant C. jejuni genotype in sheep, ST2862 (Fig. 3), was not previously identified in cattle in the United States (15,26,49). Although C. jejuni ST982 has been found in cattle (15), PFGE patterns of cattle isolates were quite different from those of the sheep isolates (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…D r a f t Inglis,Zaytsoff,Selinger,Taboada,Uwiera Canadian Journal of Microbiology Page 13 However, some evidence indicates that selection for fluoroquinolone resistance may be subtype specific including C. jejuni isolated from cattle (Cha et al 2017).…”
Section: Discussionmentioning
confidence: 99%